Applying the Values and Practical Implementation of Agricultural Science in Nigeria farming System - Nworu, Osondu Chimezie (Archives of Business Research, 2018)
No one can underrate the many significant contributions and potentials for Agriculture in the totality of the Nigerian economy. The key to developing agriculture in Nigeria is studying, researching and identify means to efficiently support the small-scale farming practiced by a majority of the populace. The paper is not advocating the abandonment of the medium and large-scale farming levels, but the small and scattered agriculture prevalently practiced has evinced the needs to empower more this category through receiving more support from aid donors and the governments. Therefore, identifying ways to encourage this level of farming is vital, though presently middle and large-scale agriculture is receiving more emphasis, which does not correspond to any visible increase of the gross national products. Also, for the fact that the above 75 percent of the population that engages in agriculture that gets up to about 95 in some urban and rural areas during the rainy season are mostly small-scale farmers. These, are the lots of the small farmers that cultivate about 90% of the 83 million hectares developed of the 98 million hectares of the arable land area. As per Nigeria, small-scale farming accounts for about 95% of total agricultural output - Federal Ministry of Agriculture, 2005 [1]. For the fact that agrarian science is such a broad multidisciplinary field, the goal to pursue is self-sufficiency in food production to enhance the lives of the masses by improving the capacity of the small-scale farmers who efficiently produce almost the food consumed through the innovative applications of some parts of the discipline of agricultural science. Notably, by applying Soil Science, and Production techniques like irrigation management, recommended nitrogen inputs, thereby improving the agricultural productivity, optimally dissemination of information and free urban/rural farming vocation skills pieces of training. Also, shall invariably enhance productivity and remove from the farmers the stress of always relying on seasonal rainfall and from the catastrophe to the ecosystem caused by the bush fallow system, especially in the Niger Delta region because of the high rate of gas flaring. Mainly this time that the UNEP in Ogoniland (topsoil) cleanup operations that are going on to improve the environment and grow healthier efficient crops for consumption.